Stability of pore-plated membranes for hydrogen production in fluidized-bed membrane reactors. (4th March 2020) - Tosto, E.; Alique, D.; Martinez-Diaz, D.; Sanz, R.; Calles, J.A.; Caravella, A.; Medrano, J.A.; Gallucci, F.
Abstract: Pd-based membranes prepared by pore-plating technique have been investigated for the first time under fluidization conditions. A palladium thickness around 20 μm was achieved onto an oxidized porous stainless steel support. The stability of the membranes has been assessed for more than 1300 h in gas separation mode (no catalyst) and other additional 200 h to continuous fluidization conditions. Permeances in the order of 5·10 −7 mol s −1 m −2 Pa −1 have been obtained for temperatures in a range between 375 and 500 °C. During fluidization, a small decrease in permeance is observed, as consequence of the increased external (bed-to-wall) mass transfer resistances. Moreover, water gas shift (WGS) reaction cases have been carried out in a fluidized bed membrane reactor. It has been confirmed that the selective H2 separation through the membranes resulted in CO conversions beyond the thermodynamic equilibrium (of conventional systems), showing the benefits of membrane reactors in chemical conversions. Graphical abstract: Image 1 Highlights: Novel Pd membranes prepared by pore-plate techniques are presented. These membranes are tested under fluidizitation conditions for the first time. Stability of these membranes is assessed for 1500 h in empty reactors. CO conversion in the FBMR is above the one obtained in conventional reactors.